Херсонесские терракоты и их художественная значимость - Шевченко, А. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Shevchenko. Chersonesus Terra-cottas and Their Artistic SignificanceThe artistic significance of Chersonesus terra-cottas is not properly examined still. Only several terra-cottas attracted attention of art historians, though there are a lot of interesting works of great talent in Chersonesus collection that were made by Chersonesus sculptors in the III—II centuries B.C. The images of Chersonesus divine beings (the Virgin, Heracles, Dionysus, Aphrodite, Apollo, Cybele) realized in terra-cottas have a lot of analogues in marble works of sculpture of Attica and Asia Minor, especially in Pergam and Smyrna. Though Chersonesus art of terra-cotta was under the influence of Asia Minor tradition, it developed independently. It was local school that inherited classical tradition of antique art and enriched it with new ideas and original local colour.